3(2x – 5)+ 5(x – 6)=-1 Solve for x

Question

3(2x – 5)+ 5(x – 6)=-1

Solve for x

in progress 0
Nick 6 months 2021-09-04T08:25:43+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-04T08:27:11+00:00

    Answer:

    x= 4

    Step-by-step explanation:

    0
    2021-09-04T08:27:12+00:00

    X=4

    How did I get this?
    3(2x-5)+5(x-6)=-1
    (6x-15)+(5x-30)
    11x-45=-1
    11x=44
    x=4

    I put it in parentheses so it’s easier to understand
    First you’re going to distribute 3 to the 2x and -5 so 6x-15. Then you will do the same with the 5 so 5x-30. Combine like terms- 6x+5x and -15-30. Once you get 11x-45=-1 move the -45 over. Since it’s negative you’re going to add. 45+-1=44. After you have moved over the -45 you should have 11x=44. Lastly you are going to divide 44 by 11 which give you your answer x=4.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )